Secure random number generation in wireless sensor networks. (6th June 2014) - Lo Re, Giuseppe; Milazzo, Fabrizio; Ortolani, Marco; Orgun, Mehmet A.; Orgun, Atilla Elçi; Pieprzyk, Josef; Chefranov, Alexander; Shankaran, Rajan; Wang, Huaxiong; Zhuge, Hai
Summary The increasing adoption of wireless sensor networks as a flexible and inexpensive tool for the most diverse applications, ranging from environmental monitoring to home automation, has raised more and more attention to the issues related to the design of specifically customized security mechanisms. The scarcity of computational, storage, and bandwidth resources cannot definitely be disregarded in such context, and this makes the implementation of security algorithms particularly challenging. This paper proposes a security framework for the generation of true random numbers, which are paramount as the core building block for many security algorithms; the intrinsic nature of wireless sensor nodes and their capability of reliably providing measurements of environmental quantities make them natural candidates as true random number generators. In order to provide robustness to common attacks, we additionally devised a protocol aimed at obscuring the actual source of data, by making nodes cooperate with their neighbors. Furthermore, we describe an enhanced version of our framework consisting in an optimization for use in the context of resource‐constrained systems. Copyright © 2014 John Wiley & Sons, Ltd.